Small RNAs Derived from the T-DNA of Agrobacterium rhizogenes in Hairy Roots of Phaseolus vulgaris - Peláez, Pablo; Hernández-López, Alejandrina; Estrada-Navarrete, Georgina; Sanchez, Federico (Frontiers in Plant Science, 2017)
Agrobacterium rhizogenes is a pathogenic bacteria that causes hairy root disease by transferring bacterial DNA into the plant genome. It is an essential tool for industry and research due to its capacity to produce genetically modified roots and whole organisms. Here, we identified and characterized small RNAs generated from the transfer DNA (T-DNA) of A. rhizogenes in hairy roots of common bean (Phaseolus vulgaris). Distinct abundant A. rhizogenes T-DNA-derived small RNAs (ArT-sRNAs) belonging to several oncogenes were detected in hairy roots using high-throughput sequencing. The most abundant and diverse species of ArT-sRNAs were those of 21- and 22-nucleotides in length. Many T-DNA encoded genes constituted phasiRNA producing loci (PHAS loci). Interestingly, degradome analysis revealed that ArT-sRNAs potentially target genes of P. vulgaris. In addition, we detected low levels of ArT-sRNAs in the A. rhizogenes-induced calli generated at the wound site before hairy root emergence. These results suggest that RNA silencing targets several genes from T-DNA of A. rhizogenes in hairy roots of common bean. Therefore, the role of RNA silencing observed in this study has implications in our understanding and usage of this unique plant-bacteria interaction.